A Study on Cluster Partitioning with Cooperative MISO Scheme in Wireless Sensor Networks. (26th March 2012) - Huang, Zheng; Okada, Hiraku; Katayama, Masaaki; Yamazato, Takaya
Abstract : This paper addresses the cluster partitioning problem in wireless sensor networks deployed in a continuous area. We present the model of the network and describe its operational details firstly. Both single-hop and multihop transmissions with cooperative Multi-Input Single-Output (MISO) scheme are considered for the intercluster communications. Besides, uniform and linear data fusions are discussed. Then, the calculations of energy consumptions are derived. Different from other researches, the energy consumptions of intracluster communication in each cluster are included and modeled as functions of the cluster size. Finally, we simulate all possible cluster partitions by changing the numbers of clusters and cooperative transmitting nodes and find the maximal network lifetimes. As a result, the relationships between cluster partitions and network lifetimes are clarified in different situations.